POTENSI BAHARI PULAU DERAWAN MENUJU DESTINASI WISATA KOMPETITIF - Dadang Ilham Kurniawan Mujiono (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
As a nation Indonesia famous throughout the world as archipelago state, and those islands provide plenty of tourist destinations. Nowadays, the power of nations unlike in cold war era, where traditional security is measured as the main source of power, however in today’s society non-traditional security become the main power, and one of them is tourism. As a country located in the coral triangle, Indonesia is surrounded by the shallow tropical marine ecosystem, where corals, fishes and other marine creatures are abundant. Indonesia in addition is the biggest contributor for the coral triangle area and Raja Ampat hosting the highest diversity of Marine world followed Derawan Island in East Kalimantan as the second place. This scientific paper will explain the potency of Derawan Island toward the competitive destination. In order to analyse the topic, the concept of hospitality will implement and the type of data research is primary, since the author conducting field research in Derawan Island and visiting number of official government agencies which related with the topic of research. The type of the research is descriptive explanative where the author will describe the data and explain about the potency of Derawan Island. The research shows that Derawan Island is located in the epicentre of marine biodiversity of the coral triangle. In addition Derawan Island also hosting two of six marine turtles in the world such as hawksbill and green turtle, in terms of dive spot, there are plenty of locations as the dive spot followed with extraordinary view and diversity of underwater world. Moreover related with accommodation, there are plenty of guesthouses, hotels and cottages and tourist can choose based on their budget.